Computational Modeling of the Value Co-Creation Process in Customer Service: An Application of the NK Model - Li, Xi; Sekiguchi, Tomoki; Wu, Jiunyan; Ye, Qiongwei (Frontiers in Psychology, 2022)
Knowledge on explore customer engagement behavior increasing interest among academia and practitioner. Specially, the value co-creation process in customer services is essentially to explore the interaction structure. In this study, we applied the computational simulation of the NK model to identify the value co-creation process between service employees and customers in the service context. Specifically, to explore the dynamic interaction among them, we identified what kind of service is provided for what type of customers and when service performance improves according to the degree of interaction between service employees and customers. The simulations show that the greatest service value can be achieved when employees and customers jointly perform local search (90%) and long jump (10%). However, if both employees and customers jointly perform local search only, the service value can be stuck in a local optimum. In cases where employees and customers make their independent improvement, either through local search or long jump, the overall service value varies depending on the complexity of interactions between employees and customers. For example, the improvement in service value is the worst when employees and customers make long jumps at independent timings in a high complex interaction. Our computational simulations offer visible experimental-based insights into understanding value co-creation process with customers and promising results for customer service studies.